Electron Microscope Study of Length and Partial Denaturation of Rhizobium Bacteriophage DNA - Mayer, Frank (1973)
By electron microscopy and melting of the DNA of some bacteriophages from the soil bacterium Rhizobium lupini, it was found that molecular weights range between 27 and 50 Mdaltons and GC contents between 53 and 62%. All DNAs studied are linear; one has exposed single-stranded terminals. Partial heat denaturation of two phage DNA permitted mapping of AT-rich sites within unique nucleotide sequences. The maps are asymmetric with respect to the midpoints of the DNA.